Characterization of the Main Character in the Film Isi & Ossi by Oliver Kienle - Mohamad Rivaldi; Melky Ayu Wijayanti; Ellychristina D. Hutubessy (Universitas Negeri Malang, 2026)
This study aims to identify and describe the characterization of the main characters in Oliver Kienle’s film Isi & Ossi. The research employs a descriptive qualitative approach, applying Minderop’s theory of fictional characterization and the Hippocrates–Galen personality typology. The findings reveal that 20 data points were collected from the two main characters in the film, consisting of dialogues, monologues, and scenes. The main characters analyzed in this study are Isi and Ossi. Based on the analysis using Minderop’s theory, the indirect characterization method appears 31 times, while the direct characterization method appears three times. Furthermore, the personality typology analysis indicates that Isi’s dominant personality type is choleric, followed by melancholic and sanguine. Meanwhile, Ossi’s dominant personality type is choleric, followed by melancholic, sanguine, and phlegmatic.